ANALISIS KUALITAS WEBSITE BOSARA TERHADAP KEPUASAN PENGGUNA DI KOTA KENDARI DENGAN MENGGUNAKAN WEBQUAL 4.0 - Iftitah, Insiyatul; Suryani, Erma (ITB AAS Indonesia Surakarta, 2024)
Along with the advancement of human civilization, information technology has experienced rapid development throughout the world, including Indonesia. This increase is reflected in the use of information technology, especially internet services as functional support. In accordance with the direction of the President of the Republic of Indonesia regarding national policies and strategies for developing e-government, it is expected that the government will be able to provide efficient, effective, accountable, and transparent services. One of the implementations is through the use of websites in various institutions, both government and non-government. Bosara is one of the websites owned by the Southeast Sulawesi Provincial Government and has been implemented as an online shopping platform for the people of Southeast Sulawesi. This study aims to analyze user satisfaction in using the Bosara website service. Website quality analysis will be carried out using Webqual 4.0 as an evaluation tool. The population and sample involve regional employees, UMK actors, district/city OPDs, and several other users who use the website. The analysis method involves descriptive statistical analysis, Webqual Index analysis, and Partial Least Square (PLS). The results of this study indicate that the variables usability quality, information quality, service interaction quality, and visual quality significantly affect user satisfaction with the quality of the Bosara website (p-value